Training to Utilize Social Media to Increase Awareness and Influence Purchasing Decisions - Lubis, Fauzi Arif; Azara, Pira; Fatin, Diyanah (Taqaddum: Community Service Journal, 2023)
Social media has become an integral part of daily life and plays a crucial role in consumer purchasing decisions. This article examines the optimization of purchasing decisions for SOMETHINC products among the community in Medan through the utilization of social media. The methods used in this service include Deep Interviews, Training, Focus Group Discussions (FGD), and Collaboration. Deep Interviews are conducted to explore consumer perspectives on social media strategies and their impact on purchasing decisions. Training is provided to the SOMETHINC marketing team to enhance interaction with consumers. FGDs gather feedback from consumers and the marketing team regarding consumer needs and preferences. Collaboration with influencers aims to expand promotional reach and increase consumer engagement. The results of the service show that although SOMETHINC has been effective in leveraging social media, there are opportunities to improve engagement with consumers. Training and the implementation of new, more personal and interactive strategies have successfully increased consumer loyalty and the impact of social media on purchasing decisions. FGDs and collaboration with influencers have contributed to refining promotional strategies and expanding market reach. Therefore, the company needs to develop relevant content, actively interact with consumers, and leverage influencers to enhance awareness and the influence of social media on purchasing decisions.